Virtual Simulation-Based Training and Person-Centered Care - Christen Page; Morgan Blaydes; Leah Simpkins; Casey Humphrey; Kellie Ellis (Journal of the Scholarship of Teaching and Learning, 2024)
Person-centered care is instrumental in the treatment of individuals with dementia.  Despite this finding, research on the efficacy of training future healthcare providers to implement person-centered care for individuals with dementia is limited.  Simulation-based education serves as one training method, but its effects of preparing students to treat persons with dementia using person-centered care is unknown. This mixed methods study used short-term treatment goals, reflective essays, and focus groups to evaluate the difference prior to and after a virtual reality dementia experience in graduate Communication Sciences and Disorders’ students’ perceptions of person-centered care.  Findings support the theory that a virtual reality dementia experience impacts students’ intent to provide PCC for persons with dementia.  More research is warranted to determine whether a virtual reality dementia experience effectively facilitates the use of PCC in the clinical setting.